PENGEMBANGAN RANCANG BANGUN SISTEM KESISWAAN DENGAN MENGGUNAKAN FRAMEWORK MVC (MODEL VIEW CONTROLLER) - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
In the student system requires ease in processing student data and improve the quality of school education. Schools are required to be able and able to make development efforts in terms of school management such as by conducting student administration. So the author makes the design of this student system to be more easily developed and using the pattern of architecture model view controller (MVC). This section of the model is used to define a way in which data can be accessed, the view portion generates output when given data, and the controller receives commands and sets the application for tasks and displays that match the school's wishes. This design prescribes a system development methodology that is with Prototype, with several stages,Stages (1): collecting user needs, where the researcher collects all the necessary data and makes the design the user wants. Stages (2): researchers create a prototype that is by designing temporary designs form. Stage (3): after making prototype then researcher do prototype test for design to be used and result from output required by user. Stages (4): evaluate the system from the design result already made, whether there is any change in the interface form. Stage (5): system usage, where all system is ready to use and according to user wishes. The result of this design is a student system based on all student administration, school curriculum activities and some other data processing.